High critical current STAR® wires with REBCO tapes by advanced MOCVD. (1st May 2023) - Galstyan, Eduard; Kadiyala, Janakiram; Paidpilli, Mahesh; Goel, Chirag; Sandra, Jithin Sai; Yerraguravagari, Vamsi; Majkic, Goran; Jain, Rohit; Chen, Siwei; Li, Yi; Schmidt, Robert; Jaroszynski, Jan; et al.
Abstract: RE–Ba–Cu–O (REBCO, RE = rare earth) symmetric tape round (STAR ® ) wires of 1.5–2.5 mm diameter have been fabricated with 4–12 strands of symmetric REBCO tape made by advanced metal organic chemical vapor deposition (MOCVD). 1.5 mm diameter STAR ® wires made with just four advanced MOCVD tape strands are able to sustain nearly the same critical current ( I c ) as 2.5 mm diameter wires made with 12 commercial-grade tape strands. An I c of 1070 A, corresponding to an engineering current density ( J e ) of 597 A mm −2, has been demonstrated at 4.2 K, 30 T in 1.5 mm diameter, four-strand wire at a bend radius of 15 mm. This I c value exactly matches the I c expected from the lift factor of the tape strands used in the wire. The 2.5 mm diameter STAR ® wires made with 12 advanced MOCVD tape strands exhibit an I c of 1075 A at 77 K, self-field and sustained currents of 2500–2750 A at 4.2 K, 30 T before burnout, corresponding to a J e greater than 500 A mm −2 . These results show that the cost of STAR ® wires can be substantially reduced using fewer tape strands of high-performance advanced MOCVD tapes and that the superior bend performance of STAR ® wires can be maintained, even using 12 strands of advanced MOCVD tapes with 4 μ m thick REBCO films.